Period Pain among Female University Students in Jeddah City, Saudi Arabia: Cross-Sectional Study - Raghad Almslamani; Lujain Hassan; Samah Alshehri; Manar Lashkar; Khalid Eljaaly; Mohannad Alshibani; Mohammed Z. Nasrullah (IMR Press, 2023)
Background: The aim of this study is to assess female college students' behavior in Jeddah, Saudi Arabia toward menstrual pain (dysmenorrhea) and their knowledge regarding the proper use of over-the-counter pain medications. Methods: A cross-sectional survey-based study that assessed 300 healthy females. The major points in the questionnaire were symptoms experienced during menstruation, pharmacological and nonpharmacological pain management, effects of participants' menstrual periods on daily activity, locations of pain, menstrual pain severity, and exercise activity. Results: From the 300 participants who participated in the survey, pain was experienced by 256 (85%) of participants. Among those 256, 46.1% felt the pain was severe. The most reported pain was in abdomen (89.2%) and back (70%). Most participants (81.2%) experienced pain during the first 3 days. As for the management method, 69.9% managed their pain by nonpharmacological and 66.8% by pharmacological agents. Approximately 43% reported to practice physical activity during menstruation. Conclusions: Dysmenorrhea is common among female college students and affects their daily activity. Many students are suffering from menstrual pain and treating it with different methods. Most participants are not aware of the proper usage of pain killers. Pharmacists and other health care personnel can instruct on how to use analgesics during menstruation.